Migration Management? - Sandra Paola Alvarez Tinajero (Graduate Institute Publications, 2014)
This book takes the reader into the lives of migrant workers who perform low-status occupations in Ragusa, Sicily. By drawing parallels between the experiences of live-in care and farm migrant workers, the author reveals remarkable similarities in how they relate to the labour market, to the state, and to the employers, building bridges between two sectors of the economy often studied separately. Through extensive fieldwork and interviews with workers and employers, the author explores how st...